The effect of regulation, accountability systems, accounting principles, priority programs on performance accountability and performance reporting moderates of good financial governance of village - Wahyuandari, Wenni; Ratnawati, Tri; Riyadi, Slamet (International research journal of management, IT and social sciences, 2022)
Research to prove, analyze and interpret the Effect of Regulation, Accountability System, Accounting Principles, Priority Programs on Performance Accountability, and Performance Reports in Village Fund Management with Moderate Variables Good Financial Governance (GFG) Village. This study uses a quantitative approach by collecting data through a survey of village heads who receive village funds. This study uses an explanatory approach by testing some hypotheses. The study population was in all villages receiving village funds in Tulungagung Regency in 2021. The number of samples was determined using the Slovin formula with a tolerance of 5% as many as 156 respondents. Sampling was done using Random Sampling, while the data analysis technique used Partial Least Square. Regulation, work accountability, accounting principles partially have a significant effect on performance Reports. Priority Programs have a significant effect on Performance AccountabilityandGFG can strengthen the relationship between the Village Fund Accounting Principles and the performance report.